GROUND-STATE MAGNETIC-MOMENTS OF BI-212,BI-213 - Lindroos, M; Richards, P; Blomqvist, J; Rikovska, J; Stone, N (Kluwer Academic Publishers, 1992)
The magnetic dipole moments of212Bi and213Bi have been measured and the results are interpreted within the framework of the shell model. © 1992 J.C. Baltzer A.G., Scientific Publishing Company.